The effectiveness of schema therapy for patients with anxiety disorders, OCD, or PTSD: A systematic review and research agenda. (23rd July 2021) - Peeters, Nancy; van Passel, Boris; Krans, Julie
Abstract : Objectives: We reviewed the evidence regarding the effectiveness of schema therapy for anxiety disorders, obsessive‐compulsive disorder (OCD), and posttraumatic stress disorder (PTSD). Methods: This systematic review followed the recommendation of the PRISMA guidelines. A database search (PsycINFO, MEDLINE, EMBASE, WEB OF SCIENCE, and Academic Search Ultimate) was conducted to identify eligible studies up until 2 April 2021. The search included the keywords ('schema therap*' or 'schema group therap*' or 'schema mode therap*' or 'schema focused' or 'young's model') and ('anxiety disorder*' or 'anxiety‐related disorder*' or 'agoraphobia' or 'health anxiety' or 'phobi*' or 'panic disorder' or 'obsessive compulsive disorder' or 'OCD' or 'posttraumatic stress' or 'post traumatic stress' or 'PTSD' or 'hypochondria' or 'axis 1'). Included studies were appraised on methodological quality according to the Psychotherapy Outcome study Methodology Rating Form. Results: We identified 41 studies that were eligible based on the topic. However, only six (comprising 316 anxiety, OCD, and PTSD patients) could be included despite lenient methodological inclusion/exclusion criteria. Results showed that schema therapy can lead to beneficial effects in disorder‐specific symptoms and early maladaptive schemas. Yet, we also uncovered substantial methodological limitations in most studies. Conclusions: Schema therapy is a promising treatment for anxiety, OCD, and PTSD. Yet, there is a systematic problem in the quality of research despite growing clinical interest and application. We therefore concluded with a research agenda presenting recommendations for future research that will be crucial for building a solid evidence‐base for schema therapy in chronic anxiety, OCD, and PTSD. Practitioner points: A systematic review on the effectiveness of schema therapy for anxiety disorders, OCD, and PTSD. Preliminary but limited evidence that schema therapy leads to beneficial effects in disorder‐specific symptoms. Preliminary but limited evidence that schema therapy leads to beneficial effects in early maladaptive schemas in anxiety, OCD, and PTSD. More research of higher methodological quality is needed to provide more conclusive empirical support for the use of schema therapy for anxiety, OCD, and PTSD.